Leveraging institutional loyalty: a marketing framework for driving graduate re-enrolment in higher education - Kayal, Ghadeer G.; Billah, Syed Mabruk (Frontiers in Education, 2026)
IntroductionThis study examines the role of a formalized Customer Relationship Management (CRM) framework in improving student satisfaction and loyalty within a non-profit private university in Saudi Arabia. Drawing on reciprocity and relationship marketing theories, the research investigates how CRM tools, including multi-tiered feedback systems and key performance indicators (KPIs), shape student experiences and influence re-enrolment.MethodsThis quantitative study utilized a longitudinal cross-sectional design, administering the same survey instrument to distinct student populations across two consecutive years. A mixed-methods design combined quantitative survey data with sentiment analysis and Latent Dirichlet Allocation (LDA) of open-ended responses.ResultsResults reveal a positive correlation between CRM-driven service quality and student satisfaction. These findings indicate that a formalized framework fosters student loyalty and encourages higher rates of postgraduate enrollment.DiscussionThe study contributes to CRM literature in higher education by demonstrating the efficacy of relationship marketing in a non-profit academic context. It offers a replicable model for institutions seeking to enhance student relationships, improve strategic service delivery, and boost overall institutional performance.